Bayanullah (Menuju Sikap Terbuka;Hukum Islam di Kesultanan Ternate) - Usman Nomay (AL-TADABBUR, 2018)
This aticle is a study of Ternate history by using the religious perpektive as a tool in order to present a historical as humanism. This study indicates that sultan Bayanullah is a good, sincere, intellect and caring apply the law of Islam.The in efforts look after is community, as sultan Bayanullah try put in the front attitude leadership capable wised and than consistent in the law doctrine Islamic. That is look, for example, from attitude Sultan Bayanullah in consistent in apply doctrine of Islam at komunity Ternate.In the particular for helpers. The attitude it is good sultan, seem since the put of outside regulations free for  be religious to her helpers; delimitation polygamy, introduction free sex, participate in lotere, cost by wedding is appropriate is law Islam, and female must be wearing clothes by law of Islam. To it is all a reflection of a who was inspired by the teaching of Islam to build a safe, fair and prosperous civilization.